Multipart Music as Self-Determination: Perspectives and Discourses in an Arbëresh Community of Singing Women - Dattilo Delia (Journal of Ethnology and Folkloristics, 2025)
Anna Stratigò (b. 1958) is an influential singer, musician and songwriter within the landscape of Arbëresh traditional music. She organises singing gatherings where she also holds important discussions about the role of women in the practice and transmission of traditional music. She established the Vuxhë Grash (Voices of Women) choir in 2017 and has been its leader since then. The choir includes several women from the village of Lungro (Province of Cosenza, Calabria, Italy) who regularly take part in the learning and performing of songs from the Arbëresh oral tradition. The learning sessions occur in self-managed, participatory meetings where each participant has the opportunity to experience the reviving of unique songs together with others, exploring and examining the repertoire during friendly singing sessions. These gatherings serve as the heart of their music-making process.